Wind Energy Technologies for Distributed Power - Chaar, L. El; Lamont, L.A. (Journal of Technology Innovations in Renewable Energy, 2013)
This paper is an industrial update on the development of wind energy conversion systems (WECS). It highlights the two major types of wind turbines: horizontal axis and vertical axis. To enhance the integration and deployment of wind technologies, advancements in their operation have been developed specifically with regard to enhanced efficiency, making them more robust and less susceptible to wind variations. This paper encapsulates the various power ratings available in the range of 10 kW to 1 MW while providing manufacturer and technical details of such topologies. The paper also considers the future requirement potential of wind energy technology.